Ethnocentrism, universalism, and refugees' social rights: The Israeli perspective. (March 2022) - Tsfati, Maya; Ben-Ari, Adital; Lavi, Iris
This article is a pilot study in which we analyzed interviews with 16 inhabitants of the Tel Aviv area. We show that Israeli adults' views of refugees are shaped by the political discourse of threat and otherness. Yet the findings also suggest that individuals may resist the prevailing discourse and advocate for refugees' inclusion within Israeli society through the welfare regime. Thus, a gap is revealed between two perspectives that reflect current conflicting perceptions of social inclusion, the immigration regime, social rights in regard to African refugees and the character of current-day Israeli society.